Cancer Nanotechnology Basic,Translational and Clinical Research - Gu, Zi (Sophia).; Curley, Steven A.; Currell, Frederick J.; Krishnan, Sunil; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: BioMed Central.)
Cancer Nanotechnology aims to provide a platform for the researchers to share the latest advancements in the field, focusing on new nanotechnologies that promise to improve both diagnosis and treatment of cancer. The journal covers a broad range of topics in cancer treatment and diagnosis, including but not limited to: Drug delivery technology RNA and other therapeutic cargo delivery Phototherapy, chemodynamic and sonodynamic therapies Nanoparticles for early diagnosis New technologies for nanomedicine design and evaluation.
Keywords: Nanotechnology; Cancer; Biomedical engineering; Biochemistry; Nanotechnology; Cancer Biology; Biomedical Engineering and Bioengineering; Chemical Biology